1975
DOI: 10.1128/jvi.16.2.222-227.1975
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in bacteriophage R17 and its RNA

Abstract: Bacteriophage R17 and its RNA were found to contain significant amounts of spermidine but not of putrescine. When isolated at 0.01 M KCl, up to 1,000 molecules of spermidine were associated with the virion. The phage RNA isolated with phenol plus sodium lauryl sulfate contained approximately 70 to 90 molecules of spermidine. The association appeared to be ionic because the bound spermidine could be dissociated by KCI, MgCl2, or both. Effects of polyamines on in vitro translation were studied using both poly(U)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Polyamines are ubiquitous molecules found in all cells at concentrations up to 1 mM (Igarashi and Kashiwagi, 2000); thus, viruses may have evolved a dependence on polyamines. Polyamines are enriched in virions of bacteriophage T7 (Fukuma and Cohen, 1975), herpes simplex virus 1 (Gibson and Roizman, 1971), and vaccinia (Lanzer and Holowczak, 1975), among others (Fukuma and Cohen, 1975;Gibson and Roizman, 1971;Lanzer and Holowczak, 1975), but not within the virion of the RNA virus Semliki Forest virus (Raina et al, 1981). For DNA viruses, polyamines facilitate viral assembly of HCMV virions (Gibson et al, 1984), DNA-dependent RNA polymerase activity in vaccinia virus (Moussatché , 1985), and DNA synthesis in HSV-1 (Pohjanpelto et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamines are ubiquitous molecules found in all cells at concentrations up to 1 mM (Igarashi and Kashiwagi, 2000); thus, viruses may have evolved a dependence on polyamines. Polyamines are enriched in virions of bacteriophage T7 (Fukuma and Cohen, 1975), herpes simplex virus 1 (Gibson and Roizman, 1971), and vaccinia (Lanzer and Holowczak, 1975), among others (Fukuma and Cohen, 1975;Gibson and Roizman, 1971;Lanzer and Holowczak, 1975), but not within the virion of the RNA virus Semliki Forest virus (Raina et al, 1981). For DNA viruses, polyamines facilitate viral assembly of HCMV virions (Gibson et al, 1984), DNA-dependent RNA polymerase activity in vaccinia virus (Moussatché , 1985), and DNA synthesis in HSV-1 (Pohjanpelto et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The viral capsids of herpesviruses contain polyamines that putatively neutralize charges on viral DNA to facilitate compaction and encapsidation (Gibson and Roizman, 1971). Vaccinia (Lanzer and Holowczak, 1975) and bacteriophage R17 (Fukuma and Cohen, 1975) were also shown to incorporate polyamines into virions. While RNA viruses could potentially use similar mechanisms to neutralize nucleic acids, studies on Semliki Forest virus demonstrated that polyamines are not enriched in the viral capsid (Raina et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Virions from densonucleosis viruses 1 and 2 contain putrescine, spermidine, and spermine comprising 1.41% ( w / w ) of the virus particle and neutralizing 26% of the single-stranded viral DNA [ 129 ]. Vaccinia virus of the Poxviridae family [ 130 ] and bacteriophage R17 [ 131 ] also incorporate polyamines into virions. Encephalomyocarditis virus contains approximately 200 molecules of putrescine, 100 molecules of spermidine, and 40 molecules of spermine that neutralize 11% of the negative charge of the viral genome [ 132 ].…”
Section: Biogenic Polyamines At the Crossroads Of Redox Statusmentioning
confidence: 99%
“…It has been claimed that the RNA phage R17 contains about 1000 molecules of spermidine which are sufficient to neutralize the phosphate groups completely. A certain fraction of these ions remains bound to the RNA after isolation depending on the conditions used (Fukuma & Cohen, 1975). The presence of a chelating agent like EDTA will not be sufficient to overcome the above-mentioned problems, so dialysis of the RNA solutions and dilution with dialysate should be necessary steps in the physicochemical characterization of natural RNAs.…”
Section: Discussionmentioning
confidence: 99%